The KOUNCIL Consortium: From Genetic Defects to Therapeutic Development for Nephronophthisis - Renkema, Kirsten Y.; Giles, Rachel H.; Lilien, Marc R.; Beales, Philip L.; Roepman, Ronald; Oud, Machteld M.; Arts, Heleen H.; Knoers, Nine V. A. M. (Frontiers in Pediatrics, 2018)
Nephronophthisis (NPH) is the most common monogenic cause of renal failure in children. Treatment options are limited to dialysis and transplantation. Therapeutics to significantly delay or prevent end-stage renal disease (ESRD) in children are currently not available. In the Dutch-Anglo KOUNCIL (Kidney-Oriented UNderstanding of correcting CILiopathies) consortium, several groups and specialties united to perform scientific groundwork with the aim to develop genetic and therapeutic personalized care for NPH patients. At the start of this consortium, a genetic diagnosis for NPH was available for only 30–40% of patients, which improved to 50–60% during the course of the 4-year KOUNCIL project. Other major accomplishments of the consortium were (1) the establishment of a Dutch renal ciliopathy patient database with genotype and phenotype data; (2) composition of a proteomics-based integrated network of protein modules disrupted in NPH; (3) the development of non-invasive, urine-based assays that allow functional assessment of genomic variants in NPH and of therapeutic efficiency of drugs; and (4) chemical screening toward the identification of compounds that delay or prevent disease progression in NPH, which resulted in four potential medical interventions for NPH. In conclusion, the KOUNCIL consortium effectively channeled complementary approaches to broaden our understanding of NPH pathogenesis, resulted in 54 publications, improvement of genome diagnostics for NPH patients, awareness in the nephrology and clinical genetics communities for NPH, and new avenues for patient management.